The Role of Senescence-Associated Secretory Phenotype in Bone Loss - Zhu, Runjiu; Wan, Haoyang; Yang, Hong; Song, Mingrui; Chai, Yu; Yu, Bin (Frontiers in Cell and Developmental Biology, 2022)
As the population of most nations across the world ages, more and more individuals are developing osteoporosis. As a result, scientists have focused their attention on the pathogenic mechanism of osteoporosis. Due to an increase in studies on cellular senescence in recent years, we have progressively begun to focus on the function of the senescent micro-environment in osteoporosis. In the presence of chronic inflammation, senescent cells in the bone marrow cavity secrete a series of factors known as senescence-associated secretory phenotype, which act on their own or surrounding healthy cells in a variety of secretory ways and exacerbate their own aging or induce aging in surrounding healthy cells. The components of senescence-associated secretory phenotype may alter depending on the cause of osteoporosis, but the results are generally the same. Therefore, we summarize the relationship between senescence-associated secretory phenotype and osteoporosis with the ultimate goal of providing some new thoughts for investigation of osteoporosis mechanistically.